2015
DOI: 10.1088/0953-4075/49/1/015602
|View full text |Cite
|
Sign up to set email alerts
|

Near-circularly polarized single attosecond pulse generation from nitrogen molecules in spatially inhomogeneous laser fields

Abstract: The generation of an attosecond pulse in nitrogen molecules using spatially inhomogeneous laser fields is investigated by numerically solving the time-dependent Schrödinger equation. It is found that an isolated attosecond pulse with elliptical polarization can be generated using linearly polarized laser fields. By changing polarization direction with respect to the molecular axis, the ellipticity of the attosecond pulse can be easily controlled. At some specific angles, the intensities of the two mutually ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…As seen, (i) when + H 2 is injected into the gap center (z 0 = 0.0), the laser enhancement presents the symmetry in the negative-z and the positive-z. As a result, the harmonic cutoff beyond the classical value of I p + 3.17U p should be obtained [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Through our calculations, the higher pulse intensity is, the larger extension of the harmonic cutoff will be.…”
Section: Methodsmentioning
confidence: 73%
See 2 more Smart Citations
“…As seen, (i) when + H 2 is injected into the gap center (z 0 = 0.0), the laser enhancement presents the symmetry in the negative-z and the positive-z. As a result, the harmonic cutoff beyond the classical value of I p + 3.17U p should be obtained [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Through our calculations, the higher pulse intensity is, the larger extension of the harmonic cutoff will be.…”
Section: Methodsmentioning
confidence: 73%
“…In 2008, Kim et al [15] first reported that the HHG can be generated and extended from the plasmon-enhanced nonhomogeneous field, which can be produced when the bow-tie metallic nanostructures is illuminated by a lowintensity laser pulse. Further, the investigations of the HHG in the nonhomogeneous field receive lots of attention due to its potential to extend the harmonic cutoff [16][17][18][19][20][21][22][23][24][25][26][27][28]. In earlier stage from 2008 to 2014, the investigations of the HHG driven by the nonhomogeneous field are focus on the atomic systems [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, to overcome this weakness, many improved schemes have been proposed. For example: (i) using the two-color or the three-color combined field [8,[21][22][23][24], many improved SAPs shorter than one atomic unit can be obtained; (ii) using the polarization gating scheme [25][26][27][28][29], a number of SAPs can be obtained when the multi-cycle driven pulses are adopted; (iii) using the inhomogeneous effect of the laser field [30][31][32][33][34][35][36][37], many SAPs can be produced in the lower laser intensity region; (iv) using the frequency-chirping technique [38][39][40][41][42][43], drastic changes in the HHG can be found, including extension of the harmonic cutoff and the enhancement of the HHG yield. Thus, many attractive SAPs can be obtained when the frequency-chirping technique is adopted.…”
Section: Introductionmentioning
confidence: 99%